Exploring the association between sleep quality, internet addiction, and related factors among adolescents in Dakshinkali Municipality, Nepal. - Sophiya Acharya; Anisha Chalise; Nirmal Raj Marasine; Shishir Paudel (PLoS ONE)
Background Poor sleep quality and internet addiction are significant issues affecting adolescents globally, and Nepal is no exception. Several studies have independently assessed the prevalence and associated factors of poor sleep quality and internet addiction among Nepali adolescents and youth, but the relationship between sleep-related attributes and internet addiction remains unexplored. This study aimed to explore the prevalence and contributing factors of poor sleep quality and internet addiction along with the relationship between sleep quality-related attributes and internet addiction. Material and methods A cross-sectional study was conducted among 243 adolescents of Dakshinkali Municipality, Nepal. Pittsburgh Sleep Quality Index and Young's Internet Addiction Test scale were used to measure sleep quality and internet addiction. Pearson's chi-square test and binary logistic regression were performed at a 5% level of significance to examine the associated factors. Results The prevalence of poor sleep quality was 27.6% (95% CI: 22.6-33.7) while potential internet addiction was 49.4% (95% CI: 42.0-56.7). Poor sleep quality was associated with internet addiction (aOR: 1.845; 95% CI: 1.344-3.608), poor perceived relation with teachers (aOR: 2.274; 95% CI: 1.149-4.497), and presence of family conflict (aOR: 2.355; 95% CI: 1.040-5.329). Bad subjective sleep quality (aOR: 5.613; 95% CI: 2.007-15.701), sleep disturbance (aOR: 1.781; 95% CI: 1.251-4.872), frequent daytime dysfunction (aOR: 1.902; 95% CI: 1.083-4.638), and poor perceived relation with teachers (aOR: 2.298; 95% CI: 1.233-4.285), and presence of family conflict (aOR: 1.606; 95% CI: 1.202-3.675) were associated with internet addiction. Conclusion Almost a quarter of adolescents' experience poor sleep quality, while nearly half screened positive for potential internet addiction. Established interrelations between sleep quality and internet usage underscore the importance of integrated intervention approaches combining lifestyle modification and family/school support to protect and promote the mental health and well-being of Nepalese adolescents.